Dual Language Books Go Digital: Storybooks Canada in French Immersion Schools and Homes - Zaidi, Rahat; Metcalfe, Robin; Norton, Bonny (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2022)
In response to Canada’s growing ethnic, cultural, and linguistic diversity, educators in French immersion classrooms are increasingly responding with enhanced cross-linguistic initiatives, and dual language books are promising resources in the promotion of multilingualism (Zaidi, 2020; Zaidi & Dooley, 2021). This paper details a research project we completed in a 2019 classroom-based qualitative case study in a French immersion school experiencing an increasing enrollment of linguistically diverse students. The researchers sought to determine if Storybooks Canada, a free digital platform with 40 dual language books in multiple languages, could help promote literacy engagement and strengthen home-school connections. Five teacher participants identified a range of features that make the platform a useful resource for promoting literacy engagement, text comprehension, learner autonomy, meaning-making, and instructional differentiation. These included (i) the multilingual features, (ii) the ability to project stories on a large screen, (iii) the audio component, (iv) the illustrations, and (v) the different levels of text difficulty. While teachers made almost exclusive use of the French language features of the site, for classroom purposes, they supported cross-linguistic uses of the platform in the home context, with a view of strengthening home-school connections.